2019
DOI: 10.1371/journal.pone.0214644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest wildfire on inner-Alpine bird community dynamics

Abstract: As major disturbance agents, natural catastrophes impact habitats, thereby maintaining the dynamics of ecological communities. Such discrete events are expected to positively affect biodiversity because they generate high habitat heterogeneity and thus numerous ecological niche opportunities. Species typical of open and semi-open habitats, which are often of high conservation concern in modern anthropized landscapes, may benefit most from recurrent natural catastrophes that regularly reset ecosystems. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, ongoing anthropogenic activities, e.g., logging and forest fires in MRFRs, may affect insect diversity and other resources required by birds for living [2,21]. Despite the fact that frugivore birds are less abundant in MRFRs, they are still important as they disperse seeds [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, ongoing anthropogenic activities, e.g., logging and forest fires in MRFRs, may affect insect diversity and other resources required by birds for living [2,21]. Despite the fact that frugivore birds are less abundant in MRFRs, they are still important as they disperse seeds [14].…”
Section: Discussionmentioning
confidence: 99%
“…Chowfin and Leslie [3] and Sodhi et al [8] also pointed out that the decrease in species richness and abundance of birds in forests is due to habitat loss. Severe habitat degradation and/or loss due to human activities may lead to local extinctions of bird species [20][21][22]. As a result, most threatened bird species across the world have been listed by the International Union for Conservation of Nature (IUCN) on the red list as critically endangered (CR), endangered (EN), or vulnerable (VU).…”
Section: Introductionmentioning
confidence: 99%
“…The median cumulative carbon dioxide and methane emissions were 257.7 Tg and 0.9 Tg, respectively, under projected climate and wildfire in Sierra Nevada of California, and also was demonstrated that climate change increases in area burned, which affects the atmosphere to ongoing decades (1, 43). Biomass burning is a major contributor to accumulate total suspended particles, which was estimated it's acute effect on asthma hospital admissions in Brazil (35). Levoglucosan is an organic compound and a unique tracer for biomass burning processes, a study showed that biomass burning activities throughout the year in Beijing led to high ambient levoglucosan concentrations and low winter to summer ratios of levoglucosan when was compared with North America and Europe (10).…”
Section: Introductionmentioning
confidence: 99%